Neighborhood variation in unsolved homicides: a retrospective cohort study in Indianapolis, Indiana, 2007-2017 - Lauren A. Magee; J. Dennis Fortenberry; Wanzhu Tu; Sarah E. Wiehe (BMC, 2020)
Abstract Background Homicide is a widely acknowledged public health problem in the United States. The majority of homicides are committed with a firearm and have long-term health consequences for family members and entire communities. When left unsolved, violence may be perpetuated due to the retaliatory nature of homicides. Improving homicide clearance rates may help prevent future violence, however, we know little about the community-level social dynamics associated with unsolved homicides. Methods This study examines the individual-and-community-level social processes associated with low homicide clearance rates in Indianapolis, Indiana between 2007 and 2017. Homicide clearance is the primary outcome, defined as if a perpetrator was arrested for that homicide case between 2007 and 2017. Individual-level variables include the victim's race/ethnicity, sex, and age. Community-level (i.e., census tracts) variables include the number of resident complaints against the police, resident complains of community disorder, income inequality, number of police interactions, and proportion of African American residents. Results In Indianapolis over a 11-year period, the homicide clearance rate decreased to a low of 38% in 2017, compared to a national clearance rate of 60%. Homicide case clearance was less likely for minority (OR 0.566; 95% CI, 0.407-0.787; p < 0.01) and male (OR 0.576; 95% CI, 0.411-0.807; p < 0.01) victims. Resident complaints of community disorder were associated with a decreased odds of case clearance (OR 0.687; 95% CI, 0.485-0.973; p < .01)., African American victim's cases were less likely to be cleared in 2014-2017 (OR 0.640; 95% CI, 0.437-0.938; p < 0.05), compared to 2007. Conclusions Our study identified differences in neighborhood social processes associated with homicide clearance, indicating existing measures on these community factors are complex. Programs aimed at improving signs of community disorder and building community engagement may improve neighborhood clearance rates, lower violence, and improve the health of these communities.